2019
DOI: 10.1111/bld.12267
|View full text |Cite
|
Sign up to set email alerts
|

What happens next? A 2‐year follow‐up study into the outcomes and experiences of an adapted Dialectical Behaviour Therapy skills training group for people with intellectual disabilities

Abstract: Accessible summary• Dialectical Behaviour Therapy (DBT) is a therapy to help people manage their feelings.• We ran a DBT group for people with an intellectual disability. The group seemed to help people feel better and manage their feelings, even after the group ended.• The group was 2 years ago. We talked to three people who went to the group to see what people still remembered from the group and if DBT was still helping them.• We think having a top-up session might help people to remember and practise ideas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Problems recalling theoretical elements are replicated by other research (e.g. Hewitt, Atkisnon‐Jones, Gregory, & Hollyman, 2019).…”
Section: Discussionmentioning
confidence: 54%
“…Problems recalling theoretical elements are replicated by other research (e.g. Hewitt, Atkisnon‐Jones, Gregory, & Hollyman, 2019).…”
Section: Discussionmentioning
confidence: 54%
“…Wark et al (2017) did not clearly indicate the time frame included in the study but similarly on follow up these researchers reported that data was captured over a period of around 3 months. Many of the studies while presenting a detailed description of study intervention did not identify an overarching research design (Bunning et al, 2017, Chen et al, 2019, Davies et al, 2015, Hewitt et al, 2019; Lancioni et al, 2020; Lynnes et al, 2009; Mirza & Hammel, 2009; Roeden et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…For example, an evaluation of a radically open DBT programme (RO-DBT) for the treatment of adolescent AN revealed that despite the adolescents enjoying exibility in treatment, structure and clarity in the skills sessions were desired. [21] Commitment is an inherent part of the standard DBT protocol [4] and was frequently described by participants. Commitment was vital for participants to be included in the MED-DBT programme for at least 12 months.…”
Section: Discussionmentioning
confidence: 99%